2021
DOI: 10.1111/ans.16682
|View full text |Cite
|
Sign up to set email alerts
|

Proposed delay for safe surgery after COVID‐19

Abstract: Background Long‐term effects after COVID‐19 may affect surgical safety. This study aimed to evaluate the literature and produce evidence‐based guidance regarding the period of delay necessary for adequate recovery of patients following COVID‐19 infection before undergoing surgery. Methods A rapid review was combined with advice from a working group of 10 clinical experts across Australia and New Zealand. MEDLINE, medRxiv and grey literature were searched to 4 October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…The exact reason as to why the search trends returned to baseline even with the subsequent COVID-19 waves cannot be fully elucidated given the nature of the retrospective study design. It is likely, however, that with the initiation of COVID-19 protocols in hospitals and surgery centres, elective cases could once again proceed in a safe fashion [3][4][5][6]. This might explain why search interest in elective hand surgery returned to baseline even with the rising COVID-19 cases in July and fall of 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact reason as to why the search trends returned to baseline even with the subsequent COVID-19 waves cannot be fully elucidated given the nature of the retrospective study design. It is likely, however, that with the initiation of COVID-19 protocols in hospitals and surgery centres, elective cases could once again proceed in a safe fashion [3][4][5][6]. This might explain why search interest in elective hand surgery returned to baseline even with the rising COVID-19 cases in July and fall of 2020.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of COVID-19 infections continues to grow worldwide, data on the impact of delayed medical and surgical care on patient-related morbidity and mortality are emerging [ 3 , 4 ]. In this study, we found that online interest in elective hand surgery remained constant from the fall of 2019 to early March 2020; however, there was a marked decrease in search trends of elective hand surgery with the sudden rise in daily reported COVID-19 cases in mid-March 2020, suggesting that interest in elective hand surgery decreased with the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery on patients infected with SARS-CoV-2 may cause postoperative morbidity and mortality 3 , 4 , and this should be understood for preoperative risk–benefit assessment. Adequate delay after infection should be allowed to ensure safety for patients undergoing elective procedures 62 , 63 . Operations on COVID-19 patients should ideally occur in designated theatres with negative-pressure ventilation 12 , and suspected COVID-19 patients should wear a surgical mask during perioperative theatre transport 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Minimally Invasive Surgery e management of surgical systems has been modified considerably at many points during the current COVID-19 pandemic [15]. Recent evidence suggests that some of these changes may need to be enduring to ensure surgical safety as COVID-19 continues to spread [16]. roughout this adaptation process, the quality of the patient education process must be maintained, particularly for high-volume procedures such as laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%